2019
DOI: 10.4103/jips.jips_144_18
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prostheses bonding using silane incorporated to universal adhesives or applied separately: A systematic review

Abstract: Currently, the long-term success of esthetic rehabilitation with ceramics is required. Hence, professional knowledge about the most indicated dental material for each clinical situation as well as its usage protocol is essential. The aim of this systematic review of clinical and laboratorial studies was to compare the bond strength of prostheses using silane incorporated to universal adhesives or applied separately. The literature search in databases “Cochrane Library,” “MEDLINE,” “Web of Science,” “Scopus,” “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
8
1
3
Order By: Relevance
“…Silane-containing adhesives that bond silica-based ceramics such as single bond universal have been developed. In addition to their benefit in reducing the operation process, the adhesives' manufacturers claim that these adhesives achieve excellent bonding properties and do not require silane treatment [50,51]. However, the effectiveness of universal adhesives containing silanes remains unclear [46,48].…”
Section: Discussionmentioning
confidence: 99%
“…Silane-containing adhesives that bond silica-based ceramics such as single bond universal have been developed. In addition to their benefit in reducing the operation process, the adhesives' manufacturers claim that these adhesives achieve excellent bonding properties and do not require silane treatment [50,51]. However, the effectiveness of universal adhesives containing silanes remains unclear [46,48].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous study has reported that water-containing or acidic pre-hydrolyzed silane coupling agents have relatively short storage period [ 1 ], and the water-contact angle of silane increases with a decrease in the bonding strength when silane and methacrylate monomers exist within a single solution [ 12 ]. It has also been reported that MDP, which is a monomer commonly contained in universal adhesives and has a pH of 2–2.7, promotes self-condensation of silanol groups in the presence of silane and neutralizes the silane [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A key finding of this study is that silane-containing universal adhesives do not achieve a high bonding strength compared to that achieved using silane separately. In addition, by using non-silane-containing universal adhesives and silane together, a higher bonding strength is achieved than that obtained using universal adhesives alone; this is possibly because acidic MDP contained in universal adhesives neutralizes silane and makes it unstable over time [ 11 ]. Thus, it is thought that silane contained in universal adhesives is practically ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em uma revisão sistemática de literatura, Melo et al (18) verificaram que o pré-tratamento da cerâmica com ácido fluorídrico seguido da aplicação de adesivos universais contendo silano não é tão eficiente quanto a aplicação do silano. Além da influência da alteração do pH na ligação entre a cerâmica e cimento resinoso, a alta viscosidade dos adesivos universais pode reduzir a penetração do agente de acoplamento nas retenções criadas pelo ácido fluorídrico.…”
Section: Discussionunclassified